Stress concentration characteristics and coefficient modification for DC04 steel with holes of finite thickness - You, Han; Zhang, Limei; Lin, Xu; Tang, Ping; Du, Qiuyue (Frontiers in Materials, 2025)
IntroductionDCO4 steel sheets with a finite thickness are the subject of this study.MethodsMaterial mechanical properties were determined through tensile and shear tests, while fracture characteristics along the thickness direction were analyzed. Scanning Electron Microscopy (SEM) observation of fracture surfaces was combined with these tests to clarify the influence of holes on the mechanical behavior of the steel sheet. Subsequently, a finite element simulation of the tensile test on steel plates was performed in ABAQUS, with plate thicknesses ranging from 0.3 mm to 1.4 mm and central hole diameters from 2 mm to 6 mm, corresponding to width-to-diameter ratios of 0.2–0.6.ResultsThe influence of hole shape on the stress concentration factor (SCF) was quantified. Relationships between sheet thickness, diameter-to-width ratio, and SCF were established. The results demonstrate that for a given diameter-to-width ratio, an optimal sheet thickness exists where the SCF stabilizes.ConclusionThese findings provide a theoretical basis and technical support for the engineering design of perforated DCO4 thin steel sheet components.